TECHNOLOGY OF COMPLEX SORPTION TREATMENT OF INDUSTRIAL WASTEWATER FROM SULPHIDE AND COPPER(II)–IONES - Khudoyarova, Olga; Ranskiy, Anatoliy; Gordienko, Olga (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2021)
Complex processing of industrial waste of individual industries, including wastewater treatment, containing sulfur anions and cations of heavy metals, in order to obtain both purified water and finished industrial products is an urgent task for today. The possibility of efficient use of regenerated mixed sorbent (AC+K), containing activated carbon (AC) and diatomaceous earth (K), for wastewater treatment of certain technological processes of chemical (petrochemical) industry and galvanic industries has been shown. The sorbent with the removed contaminants was offered to be utilized as a part of plastic lubricants of special purpose. The technological process of complex sorption treatment of industrial wastewater from sulfide and copper (II) ions includes the following main stages: sorbent regeneration; purification of sulfide-alkaline solutions; purification of washing waters of galvanic productions; obtaining plastic oils. The basic technological scheme of the site of regeneration of the spent mixed sorbent (AC+K) and purification of water-sugar solutions from organic impurities was developed. The material balance of regeneration of the spent mixed sorbent was calculated. The basic technological scheme of the site of combined treatment of industrial wastewater from sulfide and copper (II) ions, regeneration of spent industrial oils with regenerated sorbent (AC+K) and production of plastic oils has been developed. It was shown that the technology of complex sorption wastewater treatment is based on the most common technological processes - heating, cooling, adsorption and filtration and does not require complex schemes of automatic process control, and chemical equipment is typical for chemical enterprises in Ukraine. The economic effect of production of special purpose plastic oils was calculated.